The Principle of Utility in Revoking a Bankruptcy Adjudications in Bakruptcy Law - Ivida Dewi Amrih Suci; R. Murjiyanto; Mohd Zamre Mohd Zahir; Sudiyana (Universitas Negeri Semarang, 2024)
Abstract Bankruptcy law regulates the unity of assets due to bankruptcy adjudications, as stipulated in Article 64 paragraph (1) of the Bankruptcy Law, which establishes that